Sports Equipment Management System for SK Bukit Durian - Vivian Kuik Huoi Thin; Sulaiman, Rabatul Aduni (Applied Information Technology And Computer Science, 2025)
Sekolah Kebangsaan Bukit Durian is a primary school where the current process of managing sports equipment in the storeroom relies on manual records and physical logbooks, leading to inefficiencies and difficulties in tracking equipment usage. The project objectives involve designing the Sports Equipment Management System (SEMS) using an object-oriented approach, developing the system using a mobile-based approach, and testing the system using system and user acceptance testing. The system is developed using Prototyping Model and integrates Quick Response (QR) Code technology to streamline the management of sports equipment. The testing results show all system functions operated correctly and met the users’ expectations in terms of functionality, usability, and interface design. Key advantages of the system include real-time inventory monitoring, automated notifications, and efficient report generation. In the future, the system can be expanded by adding features such as equipment expiry tracking and a compensation module for lost or damaged items.